Canakinumab for the treatment of familial Mediterranean fever. (4th May 2017) - Ozdogan, Huri; Ugurlu, Serdal
ABSTRACT: Introduction : Familial Mediterranean fever (FMF) is the most frequent of all hereditary autoinflammatory syndromes. It is characterized by recurrent attacks of fever and serositis. If not treated it may be complicated with AA amyloidosis. It is caused by mutations in the MEFV gene that encodes pyrin which is involved in the regulation of IL-1β. The mainstay of treatment is colchicine, however a subset of patients requires an alternative treatment either due to inadequate response or intolerance. The accumulating data indicates that anti IL-1 drugs are effective in treating colchicine resistant FMF cases and improving their quality of life. Areas covered : This review focuses on canakinumab, a fully human anti IL-1β antibody, treatment in FMF. The data obtained from case reports, case series, two Phase II studies and an ongoing double-blind, randomized, placebo controlled Phase III trial are analyzed. Efficacy and safety profiles of canakinumab are discussed. Expert commentary : Canakinumab became the first approved therapy by the Food and Drug Administration for FMF very recently, which highlights its importance as the alternative treatment in FMF.